MODIFIKASI KARBON AKTIF SEBAGAI ADSORBEN UNTUK PEMURNIAN BIOGAS - Heru Susanto; Wishnu Wijaya; I Nyoman Widiasa (Diponegoro University, 2013)
The use of biogas as an environmentally friendly fuel is limited by the presence of CO2 and water vapor asimpurities. Therefore, biogas purification for CO2 and water vapor removal is very important step during biogasapplication. This paper presents a process for biogas purification by means of adsorption using either modifiedor unmodified activated carbon as an adsorbent. The modification was performed by passing a pure ammoniagas into activated carbon in a quartz reactor. The results showed that the adsorption process using modifiedactivated carbon decreases CO2 content in biogas up to 67.5% whereas for unmodified activated carbon was of43%. Further, the modification increased CO2 adsorption capacity from 28 to 38 mg CO2/g adsorbent. Theincrease in feed temperature decreases CO2 adsorption capacity.